ANALISIS PENGARUH PROPORSI KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL, DAN KUALITAS AUDITOR EKSTERNAL TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hartrianto, Andhikanandono; Sjarief, Julianti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This research aims to analyze the influence of proportion of independent commissioners, managerial ownership, and the quality of the external auditors against disclosure of intellectual capital. Testing was done with descriptive analysis and multiple linear regression analysis to examine the relationship between the independent variable to the dependent variable on 35 industrial consumer goods manufacturing company listed on the Indonesia stock exchange from 2012 until 2014. Measurement of intellectual capital disclosure uses the 25 items disclosure scoring method belonging to Gan, et al.             The results in this study showed that the proportion of independent commissioners and external auditor quality has an impact on disclosure of intellectual capital and its influence is positive. Meanwhile, managerial ownership has effect on disclosure of intellectual capital and its influence is negative.